2019
DOI: 10.1136/bcr-2019-229520
|View full text |Cite
|
Sign up to set email alerts
|

An EBV+ lymphoepithelioma-like cholangiocarcinoma in a young woman with chronic hepatitis B

Abstract: Epstein-Barr virus (EBV) is implicated in the tumorigenesis of a variety of malignancies, including Burkitt’s lymphoma, Hodgkin’s disease and nasopharyngeal carcinoma (NPC). EBV+ lymphoepithelioma-like cholangiocarcinoma (LELCC) is a rare type of intrahepatic cholangiocarcinoma with a distinct pathology and poorly understood treatment options. Morphologically, this neoplasm resembles undifferentiated NPC, a commonly EBV+ tumour with a prominent lymphoid infiltrate. Almost all of the current literature regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Ling et al [10] retrospectively analyzed 40 cases of LELCC and found 80.0% of these cases were related to EBV. To date, only 29 cases of LELCC with Epstein-Barr Virus(EBV) Infection have been reported in the English literature [11], in addition, the diagnosis and differential diagnosis of LELCC are rarely reported [1,11]. The diagnosis and differential diagnosis of this extremely rare tumor are important for its identification.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ling et al [10] retrospectively analyzed 40 cases of LELCC and found 80.0% of these cases were related to EBV. To date, only 29 cases of LELCC with Epstein-Barr Virus(EBV) Infection have been reported in the English literature [11], in addition, the diagnosis and differential diagnosis of LELCC are rarely reported [1,11]. The diagnosis and differential diagnosis of this extremely rare tumor are important for its identification.…”
Section: Introductionmentioning
confidence: 99%
“…6,Other less likely neoplasms were also ruled out using immunohistochemistry, including inflammatory myofibroblastic tumour (Anaplastic lymphoma kinase (ALK)), malignant melanoma (HMB45 and S100) and histiocytic sarcoma (CD163). These tumours can have large cells with a lymphocyte-rich tumour stroma, but EBV were negative in situ hybridization [11] .…”
mentioning
confidence: 99%
See 3 more Smart Citations